Analysis of the Influence of Individual Characteristics, Job Characteristics, and Situational Characteristics on Employee Performance: A Case Study of the State Civil Servant Agency - Rinanda Ayu Octaviani (Privietlab, 2021)
Good performance is needed to achieve organizational objectives, including government organizations such as the bureaucratic State Personnel Board. Civil Servants are expected to perform well so that public service can be implemented. Performance, an important factor in the success of an organization, is influenced by various factors, such as individual characteristics, job characteristics, and work situation characteristics. Therefore, this study was conducted to determine the extent to which individual characteristics, job characteristics, and the characteristics of the work situation influence employee performance at the State Personnel Board. This study aimed to determine the characteristics of the individual, job, and employment situation of BKN civil servants, as well as the extent to which the influence of individual, job, and work situation characteristics on employee performance at the State Personnel Board. Methods of data collection using primary and secondary data from 90 respondents, while collecting data through questionnaires, interviews, direct observation on the object under study, and the research literature, methods of analysis using quantitative and qualitative data to test the level of significance of the effect of individual characteristics, job characteristics, and characteristics work situation on employee performance at the State Personnel Board. The overall results indicate that individual characteristics, job characteristics, and the characteristics of the work situation have either partial or simultaneous positive and significant effects on the performance of employees in the State Personnel Board.